2014
DOI: 10.3233/bme-141099
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fatty proportion in fatty liver using least squares method with constraints

Abstract: Backscatter and attenuation parameters are not easily measured in clinical applications due to tissue inhomogeneity in the region of interest (ROI). A least squares method(LSM) that fits the echo signal power spectra from a ROI to a 3parameter tissue model was used to get attenuation coefficient imaging in fatty liver. Since fat's attenuation value is higher than normal liver parenchyma, a reasonable threshold was chosen to evaluate the fatty proportion in fatty liver. Experimental results using clinical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…4. For echo attenuation to discriminate fatty liver disease, the optimal cut-off value is 0.69 dB/MHz/cm in our study and it is consistent with the previously reported work [18]. Furthermore, Table 5 clearly manifests the significant improvement from the model by combining all the parameters.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…4. For echo attenuation to discriminate fatty liver disease, the optimal cut-off value is 0.69 dB/MHz/cm in our study and it is consistent with the previously reported work [18]. Furthermore, Table 5 clearly manifests the significant improvement from the model by combining all the parameters.…”
Section: Resultssupporting
confidence: 90%
“…The accuracy as 76% for echo attenuation increased to 90% as for the established model. Since echo attenuation is comparable with the B-mode assessment by experienced doctors [18], the proposed learning-based model can help significantly increase the accuracy of the diagnosis of fatty liver disease for clinical practice. For the outputs of the established model, the optimal cut-off value is 6.6%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods assume total attenuation as a function of attenuation coefficient in an exponential form. Then an echo signal from a well-characterized reference target is utilized and the attenuation coefficients can be estimated for the processed target [8]. However, parenchyma heterogeneity may negatively impact these methods.…”
Section: Introductionmentioning
confidence: 99%